2018
DOI: 10.1007/s00464-017-6006-y
|View full text |Cite
|
Sign up to set email alerts
|

Why laparoscopists may opt for three-dimensional view: a summary of the full HTA report on 3D versus 2D laparoscopy by S.I.C.E. (Società Italiana di Chirurgia Endoscopica e Nuove Tecnologie)

Abstract: BackgroundThree-dimensional view in laparoscopic general, gynaecologic and urologic surgery is an efficient, safe and sustainable innovation. The present paper is an extract taken from a full health technology assessment report on three-dimensional vision technology compared with standard two-dimensional laparoscopic systems.MethodsA health technology assessment approach was implemented in order to investigate all the economic, social, ethical and organisational implications related to the adoption of the inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
(32 reference statements)
0
21
0
1
Order By: Relevance
“…Although the need for a complete specimen is unaltered, variation in perineal and low rectal technique could have directly influenced histopathology results. The health economics of 3D laparoscopy have not been sufficiently reported to date although a recent health technology assessment suggested the additional cost per patient for 3D systems in general surgery could be as low as €1.67 [15]. Our data suggest no meaningful secondary impact on healthcare resources could be expected.…”
Section: Discussionmentioning
confidence: 67%
“…Although the need for a complete specimen is unaltered, variation in perineal and low rectal technique could have directly influenced histopathology results. The health economics of 3D laparoscopy have not been sufficiently reported to date although a recent health technology assessment suggested the additional cost per patient for 3D systems in general surgery could be as low as €1.67 [15]. Our data suggest no meaningful secondary impact on healthcare resources could be expected.…”
Section: Discussionmentioning
confidence: 67%
“… 37 In contrast, Vettoretto and colleagues reported that adaption of the 3D system saves money for hospitals based on reduction in the operating time. 38 However, other investigators failed to find any significant difference between 2D and 3D laparoscopic surgeries concerning total surgical expenses. 27 , 28 On the other hand, discomfort, nausea, dizziness, and eye strains are among the reported limitations associated with the old generation of the 3D laparoscopic system.…”
Section: Discussionmentioning
confidence: 96%
“…49 Although the purchase of a 3D imaging system can be up to 66% more expensive than a conventional 2D laparoscopic system, 50 eventually 3D imaging systems have shown a considerable benefit in terms of blood loss, operative time, and hospital stay, resulting in a reduction of the costs associated with the intervention. 50,51 In addition, improved depth perception, surgical precision and hand/eye coordination with 3D laparoscopic systems allow for reduced surgery time, thus reducing cost, exposure time to anesthesia and morbidity. 51,52 This means better patient safety and therefore shorter hospitalization time and lower costs related to postoperative hospital stay.…”
Section: Author Evaluation Resultsmentioning
confidence: 99%